Pulmonary Fibrosis after Pegylated Liposomal Doxorubicin in Elderly Patient with Cutaneous Angiosarcoma - Marco Mazzotta; Raffaele Giusti; Daniela Iacono; Salvatore Lauro; Paolo Marchetti (Case Reports in Oncological Medicine)
Introduction. Angiosarcoma is a rare cancer of the inner lining of blood vessels and can arise anywhere in the body, most commonly presenting as cutaneous disease in elderly patient, involving head and neck (H&N), especially the scalp. Pegylated liposomal doxorubicin (PLD) is one of the available treatments in patients with advanced or metastatic disease. Common toxicities are myelosuppression, palmar-plantar erythrodysesthesia, nausea, and stomatitis. Regarding PLD-related pulmonary fibrosis in an uncommon toxicity, there are few cases reported in literature. None of these occurred in angiosarcoma. Methods. This is a case report describing an elderly patient treated with PLD for advanced H&N cutaneous angiosarcoma who developed G5 pulmonary toxicity after the second PLD administration. Results. According to our data and patient clinical outcome, we believe that she passed away from fatal PLD-induced pulmonary fibrosis. This is the first case of fatal interstitial pneumonitis in a 77-year-old woman treated with PLD for angiosarcoma. The case has been reported for its rarity. Conclusions. Pathophysiology of this phenomenon is still unclear and more studies are necessary to understand the true incidence of pulmonary toxicities in patients in treatments with PLD and its mechanism.